PENINGKATAN KAPASITAS MASYARAKAT DALAM PENCEGAHAN DBD MELALUI EDUKASI 3M BERBASIS IKANISASI DAN KADERISASI DI RW 04 DUSUN WONOREJO, DESA SIDOMULYO - Reny Nugraheni; Nofita Sari, Ana Miftahul Khoir, Bintang Aisyah Putri, Dinda Satya Larasati, Hanna Haryani, Iis Nur (Adiba Aisha Amira, 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease that remains a public health challenge, partly due to low compliance with the 3M behavior (Draining, Covering, and Recycling) at the household level. This community service program aimed to strengthen the capacity of residents in RW 04, Dusun Wonorejo, Sidomulyo Village, in preventing DHF through 3M education combined with the approaches of larva-eating fish distribution (ikanisasi) and local health cadre empowerment. The program was conducted from May 26 to June 14, 2025, using participatory, educational, evidence-based, community-driven, and empowerment-oriented approaches. The methods included an initial needs assessment through surveys, cadre training using the “AKTIF SEHAT” educational booklet accompanied by pre- and post-tests, distribution of larva-eating fish to households through door-to-door visits, verbal health education, and the installation of “Larva-Free House” stickers as visual media and participation markers. The results showed an increase in cadre knowledge from 50% to 90%, along with active community involvement in maintaining environmental cleanliness and independently replacing fish when needed. This intervention proved effective in promoting household-based preventive behavior and is recommended for replication in other areas to support sustainable dengue control efforts.